PERLINDUNGAN SAKSI DALAM BEBERAPA TINDAK PIDANA DAN PENGADILAN HAK ASASI MANUSIA - suhaimi suhaimi (Jurnal Hukum Samudra Keadilan, 2020)
Abstract, Article 184 of the Criminal Procedure Code puts witness statements first among other evidence. Witnesses in giving their statements, both at the level of investigation, prosecution and court proceedings, sometimes experience pressure, harassment, threats, terror and even violence perpetrated by certain parties. That is why witnesses need to obtain legal protection, namely as regulated in Law No. 13 of 2006 concerning Protection of Witnesses and Victims as amended by Law No. 31 of 2014 concerning Amendments to Law No. 13 of 2006 concerning Protection of Witnesses and Victims. Several criminal acts that regulate the issue of witness protection include the crime of narcotics, the eradication of corruption, the crime of terrorism and the human rights court. Legal protection for witnesses, namely in the form of protection for the witness's personal security from physical and mental threats, so that the confidentiality and identity of the witnesses should be maintained. Witness protection is intended to be able to protect witnesses from interference, threats, terror and violence against witnesses. This will be the basis for legal certainty, law enforcement, justice and the creation of a feeling of security for witnesses.